Pengaruh Latihan Sirkuit terhadap Tingkat Kebugaran Jasmani Siswa Ekstrakurikuler Bola Basket SMA Negeri 3 Cirebon - Iqbal, Muhammad; Suripto, Agus Widodo (Indonesian Journal for Physical Education and Sport, 2023)
The study aims to determine whether there is an effect of circuit training on the level of physical fitness of the basketball extracurricular students at SMA Negeri 3 Cirebon.This type of research method is quantitative with an experimental approach using a one group pretest-posttest design. The sample in this study were 15 male basketball extracurricular students at SMA Negeri 3 Cirebon. The instrument used is the Indonesian Physical Fitness Test (TKJI) with five test items, namely the 60 m sprint test, the hanging lift test, the lying down test, the upright jump test and the 1200 m run.. Data analysis technique using t-test. The results showed that (t count) was 11.309 > 1.761 (t table) with a significance value of 0.000 which was less than the significance of 0.05 (0.000 <0.05) and from the results the average value in the posttest was greater than in the pretest (15.73>12.27). Based on the results of the study, it gave a change of 28.19%. So it can be concluded that Ha is accepted and H0 is rejected, there is an effect of circuit training on the physical fitness level of the basketball extracurricular students at SMA Negeri 3 Cirebon. So it is advisable to continue using circuit training and be able to vary it with other training models according to student conditions.